Data Management in Scholarly Journals and Possible Roles for Libraries - Some Insights from EDaWaX - Sven Vlaeminck (LIBER Quarterly, 2013)
In this paper we summarize the findings of an empirical study conducted by the EDaWaX-Project. 141 economics journals were examined regarding the quality and extent of data availability policies that should support replications of published empirical results in economics. This paper suggests criteria for such policies that aim to facilitate replications. These criteria were also used for analysing the data availability policies we found in our sample and to identify best practices for data policies of scholarly journals in economics. In addition, we also evaluated the journals' data archives and checked the percentage of articles associated with research data. To conclude, an appraisal as to how scientific libraries might support the linkage of publications to underlying research data in cooperation with researchers, editors, publishers and data centres is presented.
URN:NBN:NL:UI:10-1-114595
Keywords: 330; journals; data policies; linking research data and publications